Genetic structure and diversity of squids with contrasting life histories in the Humboldt Current System - Ibáñez, Christian Marcelo; Poulin, Elie (HIDROBIOLÓGICA, 2016)
Dosidiscus gigas and Doryteuthis gahi are the most abundant squids in the Humboldt Current System (HCS). These species have contrasting life histories. To determine the genetic structure and diversity of these species, we collected samples from different places in the HCS and amplified a fragment of the mitochondrial cytochrome C oxidase I gene. The molecular analysis of D. gigas revealed low genetic diversity, absence of population structure and evidence for a demographic expansion during the transition from the last glacial period to the current interglacial. These results suggest that D. gigas is composed of one large population with high levels of gene flow throughout the HCS. In the case of D. gahi, the sequences indicated the presence of two population units in the HCS, one in south-central Chile and one in Peru. The Chilean unit had greater genetic diversity, suggesting that it is an old, relatively stable population. In the Peruvian unit there was less genetic diversity and evidence of a recent demographic expansion. The changes in distribution ranges and population sizes of the squid populations may be related to historical variations in productivity along the HCS. The different dispersion and migration capacities of these species may explain the differences in their structure; however, the genetic diversity of both species appears to be more related to historical variations in their distribution ranges and the biogeographic origin of each.